FACEBOOK: A POTENTIAL MEDIA IN TEACHING READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT TO THE ELEVENTH GRADERS OF SMAN 1 TAMAN (RETAIN, 2016)
FACEBOOK: A POTENTIAL MEDIA IN TEACHING READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT TO THE ELEVENTH GRADERS OF SMAN 1 TAMAN Getari Adyagarini English Education, Language and Arts, State University of Surabaya getariadyagarini@mhs.unesa.ac.id Ririn Pusparini, S.Pd., M.Pd. English Education, Language and Arts, State University of Surabaya rrn.puspa@gmail.com Abstrak Mengintegrasikan sosial media sebagai perantara dalam pembelajaran bahasa telah menjadi isu yang alot diperdebatkan selama dua puluh tahun terakhir oleh para ahli. Banyak penelitian menyebutkan bahwa sosial media seperti Facebook dapat digunakan sebagai media dalam dunia pendikan sesuai dengan prinsip-prinsip pedagogi yang berlaku. Namun, potensi dari Facebook sebagai media belum tereksplor maksimal, khususnya pada pembelajaran membaca komprehensif. Oleh karena itu, peneliti dalam penelitian deskripsi kualititif berikut bermaksud mengadakan penelitian yang bertujuan untuk menginvestigasi dan mendeskripsikan penggunaan Facebook grup sebagai media pada pembelajaran membaca komprehensif teks ekposisi analitis, kontribusi media ini kepada hasil ringkasan siswa, dan respon siswa terhadap penggunaan Facebook grup ini. Penelitian yang melibatkan seorang guru bahasa Inggris dan 35 siswa kelas sebelas telah berhasil mendapatkan penemuan-penemuan penting. Berdasarkan analisis dari serangkaian observasi, tugas pembelajaran memaca, dan kuisioner, Facebook grup terbukti layak dan bermanfaat untuk menbantu siswa dalam proses membaca komprehensif yang kemudian memberikan konstribusi konstruktif pada hasil meringkas siswa. Siswa juga menunjukkan respon positif terhadap praktek pelaksanaan. Key words: sosial media, facebook grup, membaca komprehensif, ringkasan Abstract Integrating social media as a means in language teaching and learning has been highlighted in the past two decades among schoolars. A number of research have argued that social media such as Facebook can be used as a media in education under pedagogic principles. However, the potential of Facebook as media has not been fully taped in Indonesia, especially in teaching and learning reading comprehension. Therefore, the researcher attempted to conduct this descriptive qualitative research with aims to investigate and describe the use of Facebook group as media in teaching reading comprehension of a specific text: analytical exposition text, its contribution to the students’ summary and the students’ responses towards the practice, The research with participants of an English teacher and 35 eleventh grade students has managed to draw some important findings. Based on the analysis of set of observations, reading task, and questionnaire, Facebook group was proven appropriate and useful to assist the students in their reading comprehension process which ultimately gave constructive contribution to the students’ summary work. The students’ showed positive attitude towards the implementation as well. Keywords: social media, facebook group, reading comprehension, summary